Seagrass Meadow Distribution Mapping in the Coastal Lagoon of Buan Island, Anambas - Dominikus Yoeli Wilson Laia; Ganang Wibisono; Eddy Handoko; Gita Endang Palufi; Fajar Kurniawan; Syofyan Roni; Muhammad Alrizky Ratno Budiarto (Jurnal Kelautan Tropis, 2023)
Seagrasses are vital monocotyledonous marine flowering plants that serve as essential food sources for megaherbivores, contribute significantly to organic carbon production, and offer a multitude of crucial ecosystem services. Preserving seagrass habitats is of utmost importance, but the lack of comprehensive spatial data poses challenges to conservation efforts. The Anambas Islands, consisting of 255 small islands in the Natuna Sea, the southern part of the South China Sea, exemplify the scarcity of seagrass data, with the current distribution map only covering the Central and East Siantan region. In this study, our aim was to map the Buan coastal lagoon, where previous visual interpretation of Google Earth imagery suggested the presence of seagrasses. To achieve this, we carried out a drone survey and collected field data to classify and map the substrate types in the study area. The field survey documented four species in the location: T. hemprichii, E. acoroides, H. ovalis and S. isoetifolium, thereby expanding the known seagrass species in Anambas to nine. By employing a pixel-based classification of orthophotos, we achieved a promising overall accuracy of 69.5%. Our findings demonstrated that imageries from the Google Earth platform are viable alternatives for identifying seagrass meadows and can be utilized to support seagrass mapping efforts. This discovery offers valuable support for future seagrass mapping initiatives, especially at a local scale. Ultimately, our study contributes to the broader understanding of seagrass distribution in the Anambas Islands, and emphasizes the importance of further exploration to support conservation efforts in the seagrass ecosystem.